Beyond Fitts's Law: A Three-Phase Model Predicts Movement Time to Position an Object in an Immersive 3D Virtual Environment. (September 2019) - Deng, Cheng-Long; Geng, Peng; Hu, Yi-Fei; Kuai, Shu-Guang
Objective: The study examines the factors determining the movement time (MT) of positioning an object in an immersive 3D virtual environment. Background: Positioning an object into a prescribed area is a fundamental operation in a 3D space. Although Fitts's law models the pointing task very well, it does not apply to a positioning task in an immersive 3D virtual environment since it does not consider the effect of object size in the positioning task. Method: Participants were asked to position a ball-shaped object into a spherical area in a virtual space using a handheld or head-tracking controller in the ray-casting technique. We varied object size (OS), movement amplitude (A), and target tolerance (TT). MT was recorded and analyzed in three phases: acceleration, deceleration, and correction. Results: In the acceleration phase, MT was inversely related to object size and positively proportional to movement amplitude. In the deceleration phase, MT was primarily determined by movement amplitude. In the correction phase, MT was affected by all three factors. We observed similar results whether participants used a handheld controller or head-tracking controller. We thus propose a three-phase model with different formulae at each phase. This model fit participants' performance very well. Conclusion: A three-phase model can successfully predict MT in the positioning task in an immersive 3D virtual environment in the acceleration, deceleration, and correction phases, separately. Application: Our model provides a quantitative framework for researchers and designers to design and evaluate 3D interfaces for the positioning task in a virtual space.